Latino Families' Experiences with Autism Services: Disparities, Capabilities, and Occupational Justice - Angell, Amber M. (OTJR (Thorofare N J), 2016)
RATIONALE: This article examines six cases of publicly-funded Applied Behavior Analysis (ABA) therapy for Latino children with autism spectrum disorder (ASD) in order to contribute to thinking about occupational justice. OBJECTIVE: We consider in each case 1) how the families' experiences can be understood occupationally; 2) how ABA affected the functionings and capabilities of the children and their families; and 3) how the parents' accounts relate to occupational justice. METHODOLOGY: This is an ethnographic study of six Latino families of children with ASD in Los Angeles County. FINDINGS: All families were offered ABA for their children, but five families experienced occupational challenges leading them to insist on modifications of ABA or opt out of the service. CONCLUSION: Applying the capabilities approach can help to operationalize the concept of occupational justice as a tool to evaluate social policy across cases.